The Beneficial Effects of Melatonin Administration Following Hypoxia-Ischemia in Preterm Fetal Sheep - Yawno, Tamara; Mahen, Mawin; Li, Jingang; Fahey, Michael C.; Jenkin, Graham; Miller, Suzanne L. (Frontiers in Cellular Neuroscience, 2017)
Melatonin is an endogenous hormone that controls circadian cycle. Melatonin has additional important properties that make it appealing as a neuroprotective agent – it is a potent antioxidant, with anti-apoptotic and anti-inflammatory properties. Melatonin is safe for administration during pregnancy or to the newborn after birth, and can reduce white matter brain injury under conditions of chronic fetal hypoxia. Accordingly, in the current study we examined whether an intermediate dose of melatonin could restore white matter brain development when administered after an acute hypoxic ischemic (HI) insult in preterm fetal sheep. Fifteen fetal sheep at 95-98 days’ gestation were instrumented with femoral artery and vein catheters, and a silastic cuff placed around the umbilical cord. At 102 days gestation, the cuff was inflated, causing complete umbilical cord occlusion for 25 min in ten fetuses, to induce acute severe HI. Five HI fetuses received intravenous melatonin for 24 h beginning at 2 h after HI. The remaining five fetuses were administered saline alone. Ten days after HI, the fetal brain was collected from each animal and white and grey matter neuropathology assessed. HI caused a significant increase in apoptotic cell death (TUNEL+), activated microglia (Iba-1+) and oxidative stress (8-OHdG+) within the subventricular and subcortical white matter. HI reduced the total number of oligodendrocytes and CNPase+ myelin density. Melatonin administration following HI decreased apoptosis, inflammation and oxidative stress within the white matter. Melatonin had intermediate benefits for the developing white matter: it increased oligodendrocyte cell number within the periventricular white matter only, and improved CNPase+ myelin density within the subcortical but not the striatal white matter. Melatonin administration following HI was also associated with improved neuronal survival within the cortex. Neuropathology in preterm infants is complex and mediated by multiple mechanisms, including inflammation, oxidative stress and apoptotic pathways. Treatment with melatonin presents a safe approach to neuroprotective therapy in preterm infants but appears to have brain region-specific benefits within the white matter.